2014
DOI: 10.1016/j.msea.2014.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of stored energy in Fe–48%Ni alloys strongly cold-rolled using three approaches: Neutron diffraction, Dillamore and KAM approaches

Abstract: The stored energy, which is the main driving energy of the primary recrystallization, was measured in two Fe-48%Ni cold-rolled samples using three different approaches: the neutron diffraction method based on the peak broadening, the Kernel Average misorientation (KAM) and the Dillamore methods both based on the misorientation and dislocation cell size estimation using EBSD (Electron Back Scatter Diffraction) data. The results were compared with each other and showed differences in stored energy values. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(25 citation statements)
references
References 28 publications
(36 reference statements)
0
25
0
Order By: Relevance
“…Based on the strain gradient model by Gao et al (1999), the authors define a GND array for a cylinder under torsion. Assuming a series of twist subgrains boundaries in the cylinder, each containing two perpendicular arrays of screw dislocations, the misorientation angle ω ik is related to KAM and the GND density by the following equation (Betanda et al, 2014):…”
Section: Appendix A: Local Misorientation Annexedmentioning
confidence: 99%
“…Based on the strain gradient model by Gao et al (1999), the authors define a GND array for a cylinder under torsion. Assuming a series of twist subgrains boundaries in the cylinder, each containing two perpendicular arrays of screw dislocations, the misorientation angle ω ik is related to KAM and the GND density by the following equation (Betanda et al, 2014):…”
Section: Appendix A: Local Misorientation Annexedmentioning
confidence: 99%
“…From Figure 4d-f, the local misorientations of the outer zone and inner zone were around 2 • , while the local misorientation of the center zone was around 1 • . Betanda et al [27] reported that local misorientation distribution maps are an effective indicator of local strain in crystal materials. Therefore, the difference in the local misorientation also confirmed the occurrence of strain heterogeneity.…”
Section: Deformation Microstructure Of the Dp Steelmentioning
confidence: 99%
“…Dislocations are comprised of geometrically necessary dislocations (GND) and statistically stored dislocation (SSD); GNDs are dislocations with the same signs which are formed in the strain gradient region and satisfy the geometrical constraints with a net non-zero Burgers vector, whereas SSDs constitutes random dislocations formed by mutual trapping process with a net zero Burgers vector during plastic deformation [26,[31][32][33][34]. According to Ashby's model for homogenous deformation of a single crystal, SSD have dominant role in work hardening.…”
Section: Introductionmentioning
confidence: 99%
“…Upon cooling, the sample temperature was stabilised at 200 o C to maintain thermal equilibrium and to minimise the thermal drift [14]. For post processing of the EBSD results, files were exported into HKL [26,32,47] to understand the difference in rate of recrystallization of respective fibres during annealing at different conditions [7,14,[28][29][30]. To evaluate a noise free GND density, the LAM value of all points were calculated and plotted based on a kernel size of 11x11 (n=5) to 3x3 (n=1) as described by Moussa et al [48].…”
Section: Introductionmentioning
confidence: 99%